Slum Area Improvement Program Based on Social Categories in Binjai City - Rangkuti, Muhammad Taufik; Sugiarto, Abdi; Abdiyanto, Abdiyanto (International Journal Papier Advance and Scientific Review, 2023)
This research aims to identify the socio-economic characteristics of the community in the Binjai Kota District, especially in the Kartini Region. It involves categorizing areas based on social and economic categories within slum areas and formulating appropriate handling strategies. The research methodology used is the SWOT Model with a descriptive and qualitative approach. Purposive sampling is employed for sample selection and informant determination. Overall, the socio-economic category of the community in the slum area tends to show low levels, as manifested in the majority having elementary school education, the dominance of laborers and farmers in the job sector, and low income levels, including land ownership with limited legality. However, there are some socio-economic categories that indicate better conditions, such as the productive age of household heads, housing density in accordance with standards, sanitation and clean water availability, and building ownership. Considering these findings, the slum area improvement program based on social categories proposed in this research should focus on strategies involving the implementation of development missions, community skill enhancement, sanitation preservation, building maintenance, and the development of non-governmental organizations. It should also encompass community empowerment, job diversification, cooperation for land ownership legality, drainage improvement, community awareness enhancement, and holistic assistance. This involves the government in the implementation of environmental cleanliness programs, collaboration between the government, regional authorities, and the community, as well as the maintenance of public facilities, improvement of community institutions, involvement of regional government within budget constraints, and collaboration between the government and the community in area arrangement.